2009
DOI: 10.1002/smll.200801303
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Viral Behavior in Mammalian Cells with Self‐Assembled Capsid–Quantum‐Dot Hybrid Particles

Abstract: Unique spectral properties of quantum dots (QDs) enable ultrasensitive and long-term biolabeling. Aiming to trace the infection, movement, and localization of viruses in living cells, QD-containing virus-like particles (VLPs) of simian virus 40 (SV40), termed SVLP-QDs, are constructed by in vitro self-assembly of the major capsid protein of SV40. SVLP-QDs show homogeneity in size ( approximately 24 nm), similarity in spectral properties to unencapsidated QDs, and considerable stability. When incubated with liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 45 publications
3
124
0
Order By: Relevance
“…The need for systemic administration of Ad therapeutics has been recognized with recent advances in nanotechnology and pharmaceutics, making it possible to engineer numerous chemical modifications of the Ad surface using polymeric materials (16,17). Originally, systemic and targeted delivery of Ads was performed by a versatile polymeric design and depot system, or by self-assembly in the pharmaceutical field.…”
Section: Ad Nanocomplexes For Systemic Deliverymentioning
confidence: 99%
“…The need for systemic administration of Ad therapeutics has been recognized with recent advances in nanotechnology and pharmaceutics, making it possible to engineer numerous chemical modifications of the Ad surface using polymeric materials (16,17). Originally, systemic and targeted delivery of Ads was performed by a versatile polymeric design and depot system, or by self-assembly in the pharmaceutical field.…”
Section: Ad Nanocomplexes For Systemic Deliverymentioning
confidence: 99%
“…QDs are light-emitting particles on the nanometer scale that have unique optical and electronic properties, including sizetunable light emission, superior signal brightness, photostability, resistance to photobleaching, and broad absorption spectra for simultaneous excitation of multiple fluorescence colors, unlike the single colors of dye molecules and fluorescent proteins (32,44). Several studies have utilized QDs to image viral behaviors in host cells (14,15,18,23,25). We expect to establish the QD labeling method as a standard cellular entry assay, and our systematic study showed that IHNV enters host cells via clathrinmediated endocytic, cytoskeleton-dependent, and low-pH-dependent pathways.…”
mentioning
confidence: 99%
“…Moreover, disassembly and reassembly of VLPs can be controlled in vitro (Mellado et al, 2009) VLPs of different viruses including cowpea chlorotic mottle virus (CCMV), the brome mosaic virus (BMV), polyomavirus (such as the Simian virus (SV40) and the human polyoma JC virus) and papillomavirus have been used, through in vitro assembly and disassembly hierarchical processes as well as through osmotic shock, to package and eventually deliver exogenous DNAs (Fang et al, 2012), oligonucleotides , peptides and proteins Kaczmarczyk, Sitaraman, Young, Hughes, & Chatterjee, 2011), small interfering RNAs and plasmids expressing short hairpin RNAs (Chou et al, 2010), small chemicals , quantum dots (Li et al, 2009) and magnetic nanoparticles (Goicochea, De, Rotello, Mukhopadhyay, & Dragnea, 2007).…”
Section: Virus-like Particlesmentioning
confidence: 99%